The Effect of Immersion Duration in Cinnamon Extract on Color Stability of Heat-Polymerized Acrylic Resin Denture Base - Veronica Angelia; Eddy Dahar; Satriawan Jodi (Dentika: Dental Journal, 2024)
Heat polymerized acrylic resin is a material that is often used as a denture base. Cinnamon extract (Cinnamomum burmannii) has the ability to inhibit the growth of Candida albicans. However, ideally, denture cleaning agents should not affect the color stability of heat polymerized acrylic resin. The aim of this study was to evaluated the effect of immersion duration in cinnamon extract simulating 1, 2, 3, 4, and 5 years of use on colour stability of heat-polymerized acrylic resin denture base. Thirty unit samples heat polymerized acrylic resin with measurment 20 x 3 mm divided into 2 groups, group A (Aquabidest) B (alkaline peroxide), and C (50% cinnamon extract). After measuring the pretest values, the samples were soaked for 5 minutes each day simulated 1, 2, 3, 4, and 5 years of use. Discoloration (âˆ†E) was evaluated using a colorimeter according to CIELAB (Commision de l'ECLAIRAGE) standards. Data were analyzed using one-way ANOVA and LSD (Least Significant Difference) statistical tests. There is an effect of immersion duration of heat polymerized acrylic resin denture base in use for 1, 2, 3, 4, and 5 years in groups A and B on colour stability 0.0001 (p<0.05). The colour change in group B was greater than that in group A, the âˆ†E value of all samples in both groups continued to increase with the length of immersion duration. However, the colour change that occurred is still clinically acceptable.